Frequency and nature of central molecular outflows in nearby star-forming disk galaxies - Krieger, Sophia K.; Saito, Toshiki; Schinnerer, Eva; Emsellem, Eric; Querejeta, Miguel; Williams, Thomas G.; Barnes, Ashley T.; Bigiel, Frank; Blanc, Guillermo; Dale, Daniel A.; Grasha, Kathryn; Klessen, Ralf S.; et al. (Astronomy and astrophysics, 2021)
Central molecular outflows in spiral galaxies are assumed to modulate their host galaxy’s star formation rate (SFR) by removing gas from the inner region of the galaxy. Outflows consisting of different gas phases appear to be a common feature in local galaxies, yet, little is known about the frequency of molecular outflows in main sequence galaxies in the nearby universe. We develop a rigorous set of selection criteria, which allow the reliable identification of outflows in large samples of galaxies. Our criteria make use of central spectra, position-velocity diagrams and velocity-integrated intensity maps (line-wing maps). We use this method on high-angular resolution CO (2-1) observations from the PHANGS-ALMA survey, which provides observations of the molecular gas for a homogeneous sample of 90 nearby main sequence galaxies at a resolution of ∼100 pc. We find correlations between the assigned outflow confidence and stellar mass or global SFR. We determine the frequency of central molecular outflows to be 25 ± 2% considering all outflow candidates, or 20 ± 2% for secure outflows only. Our resulting outflow candidate sample of 16−20 galaxies shows an overall enhanced fraction of active galactic nuclei (AGN) (50%) and bars (89%) compared to the full sample (galaxies with AGN: 24%, with bar: 61%). We extend the trend between mass outflow rates and SFR known for high outflow rates down to lower values(log10 Ṁout [M⊙ yr−1] < 0). Mass loading factors are of order unity, indicating that these outflows are not efficient in quenching the SFR in main sequence galaxies.
Gesehen am 30.11.2021